The Role of Intention to Consume in Creating Autobiographical Memory - Jony Oktavian Haryanto, Jony Oktavian (Gadjah Mada International Journal of Business, 2008)
Children are a unique and also potential market. They are unique because they usually do not spend their own money but they may have high purchasing power back-up. They are potential because from the number of kids and the amount they spend, they are big and promising. Markets for kids consist of three markets: (1) primary market that targets the children itself, (2) influence market that emphasizes the influence that the children exert on family purchases, and (3) future market that considers the future market for the children. Based on the high potential market for the children, the author identifies the impacts of intention to consume for children on influence power (an effort pursued by kids in order to frequently and successfully influence parents or people surrounding them), impulsive buying (kidsâ tendencies to buy spontaneously, immediately, and without any deep consideration), and autobiographical memory (a memory of previous experience that will be stored as a long-term memory). Furthermore, it is necessary to identify the antecedents of autobiographical memory for children. The results show that the intention to consume positively influences the impulsive buying as well as the autobiographical memory. For managerial implications, marketers need to put an emphasis on stimulating the intention to consume in order to create a positive autobiographical memory.